The Dividend Policy Moderates the Influence of Liquidity, Solvability, Profitability, and Sales Growth on the Company's Value - Kasmawati, Kasmawati; Budiyanto, Budiyanto; Agustedi, Agustedi (Riviera Publishing, 2023)
This research aims to determine and analyze dividend policy moderating the influence of Liquidity, solvability, profitability, and sales growth on company value. The method used in this research is the research approach used, namely positivist (quantitative). The population in this research is all food and beverage subsector companies in 2019 - 2021, totaling 71 companies listed on the Indonesia Stock Exchange. Based on the research results, it can be concluded that Liquidity significantly affects company value, confirming the acceptance of the research hypothesis regarding the influence of Liquidity. solvability does not significantly affect company value, so the hypothesis related to solvability is not accepted. Profitability significantly affects company value, supporting the hypothesis of the influence of profitability. Sales growth significantly affects company value, confirming the sales growth hypothesis. Dividend policy moderates the effect of Liquidity on firm value, confirming the acceptance of the liquidity-related moderation hypothesis. The dividend policy cannot moderate solvability on company value, so the moderation hypothesis related to solvability is rejected. A dividend policy can moderate the effect of profitability on firm value, supporting the moderation hypothesis related to profitability. Dividend policy moderates the effect of sales growth on firm value, confirming the acceptance of the moderation hypothesis regarding sales growth.